Continued growth, increasing complexity: Examining the evolving role of the Canadian educational developer - Laskar, Benjamin (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2021)
The improvement of teaching and learning in the Canadian post-secondary sector has grown in importance over the past fifty years as seen by the rise of the field of educational development. Educational Developers (EDs) can now be found at almost every publicly-funded college and university in the country and are increasingly integral to institutions of higher learning. However, as EDs engage in such a variety of multi-level support, it is difficult to precisely define their role. This paper will examine the role of the Canadian ED and how it has grown in complexity through an overview of the field of Canadian educational development, environmental influences on EDs, how their work is enacted, current challenges, as well as present and future directions of the role. A greater understanding of EDs will enable institutions to make effective use of these individuals, and to offer them the tailored support they require to excel.